2015
DOI: 10.1016/j.commatsci.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Uranium vacancy mobility at the Σ5 symmetric tilt and Σ5 twist grain boundaries in UO2

Abstract: a b s t r a c tIonic transport at grain boundaries in oxides dictates a number of important phenomena, from ionic conductivity to sintering to creep. For nuclear fuels, it also influences fission gas bubble nucleation and growth. Here, using a combination of atomistic calculations and object kinetic Monte Carlo (okMC) simulations, we examine the kinetic pathways associated with uranium vacancies at two model grain boundaries in UO 2 . The barriers for vacancy motion were calculated using the nudged elastic ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Conventional wisdom suggests that as mass transport is often enhanced by these microstructural features and that the kinetics of defects at these features must be higher than in the bulk. Indeed, experimental efforts have revealed that transport can be significantly faster along dislocations and boundaries in both metals and oxides. However, there is a growing body of evidence that shows that this is often not the case and that the mobility of individual defects can actually be slower at some types of interfaces, , grain boundaries, , and along dislocations. On the other hand, most studies of defect migration at grain boundaries in oxide ceramics have focused on low Σ, high symmetry boundaries . Thus, there are still unresolved questions regarding the kinetic properties of defects at grain boundaries in these materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional wisdom suggests that as mass transport is often enhanced by these microstructural features and that the kinetics of defects at these features must be higher than in the bulk. Indeed, experimental efforts have revealed that transport can be significantly faster along dislocations and boundaries in both metals and oxides. However, there is a growing body of evidence that shows that this is often not the case and that the mobility of individual defects can actually be slower at some types of interfaces, , grain boundaries, , and along dislocations. On the other hand, most studies of defect migration at grain boundaries in oxide ceramics have focused on low Σ, high symmetry boundaries . Thus, there are still unresolved questions regarding the kinetic properties of defects at grain boundaries in these materials.…”
Section: Introductionmentioning
confidence: 99%
“…10−12 On the other hand, most studies of defect migration at grain boundaries in oxide ceramics have focused on low Σ, high symmetry boundaries. 13 Thus, there are still unresolved questions regarding the kinetic properties of defects at grain boundaries in these materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Comparing single crystal tungsten and mono crystal tungsten, Valles et al (Valles et al 2017b) confirm the impact of GB on the on the amount and distribution of vacancies as well as on the migration and retention of H and propose that GB act as preferential path for H. Another study, in Al, showed, on the other hand, that diffusion of H was decreased by more than one order of magnitude in GBs (Pedersen and Jónsson 2009). In UO 2 , it was found that certain types of grain boundaries enhanced the mobility of U vacancies (Uberuaga and Andersson 2015) (Figure 11). An increase of the diffusivity of Ag and Cs in Tristructural-Isotropic (TRISO) fuel particles in high energy GB as compared to the bulk was also found by Ko et al (Ko et al 2016) (Ko et al 2017).…”
Section: Figurementioning
confidence: 90%
“…The time scale for each simulation is also indicated in the upper left corner of each frame. From (Uberuaga and Andersson 2015).…”
Section: Figure 11mentioning
confidence: 99%
“…In order to extend multi-scale modeling efforts to complex materials such as nano-grained metals, a wide range of information describing defect properties and behaviors inside grain boundaries is needed. Atomistic studies investigating a limited set of grain boundaries have obtained some defect migration energies for several metals [39,[52][53][54][55], and multi-scale studies using OKMC have been implemented for limited cases using atomistic predictions of binding and migration energies as inputs [39]. However, defect behaviors in grain boundaries depend on the specific atomic scale structure of the material interface (misorientation, defect content, etc.)…”
Section: Introductionmentioning
confidence: 99%